The role of secondary education in explaining competitiveness. Issue 1 (2nd January 2016) - Baumann, Chris; Winzar, Hume
Abstract : The literature establishes that education drives economic performance, but the extent that education is associated with a country's competitiveness is empirically untested. Our study analyses Programme for International Student Assessment (PISA) data from 63 countries to ascertain education's role in explaining the competitiveness of a country. Strong correlations were found for reading and science (each 53% shared variance) and mathematics (50%). Educational achievement explains 54% of Competitiveness. Regional differences were found with East Asia performing strongly both academically and in competitiveness, ahead of Europe, the rest of Asia, and South/Central America. Anglo-Saxon countries rank second academically behind East Asia, but in terms of competitiveness, the Anglo-Saxon cluster ranks first. We show that Anglo-Saxon countries' leadership in education and competitiveness have been challenged by East Asia. Our diachronic analysis shows that together with Competitive Industrial Performance, the cultural dimensions of Uncertainty Avoidance, Long-term Orientation and Indulgence Restraint, Education contributes to improvements in Competitiveness. The strength of East Asia in educational achievement will have implications for the region's future competitiveness compared to Anglo-Saxon and European countries. Our empirical findings support theoretical arguments for education's role in driving competitiveness. For education policy, the study emphasizes the importance of investments in reading, science and mathematics education.